2021
DOI: 10.1039/d1sm00303h
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous vesicle formation and vesicle-to-α-gel transition in aqueous mixtures of sodium monododecylphosphate and guanidinium salts

Abstract: Monoalkyl phosphates (MAPs) are one kind of important single-chain weak acid/salt type surfactants, but the understanding of their aggregation behavior in water is very limited due to their insolubility at...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…22)) indicates that a lot of water is trapped between the lamellar bilayers, similar to the previous reports. 14,25,26 Based on the above results along with our previous work, 22 it can be concluded that, microscopically, a concentration-driven stepwise aggregation occurs in the KOCOOH solution (Fig. 5).…”
Section: Structure Of Aggregatessupporting
confidence: 70%
“…22)) indicates that a lot of water is trapped between the lamellar bilayers, similar to the previous reports. 14,25,26 Based on the above results along with our previous work, 22 it can be concluded that, microscopically, a concentration-driven stepwise aggregation occurs in the KOCOOH solution (Fig. 5).…”
Section: Structure Of Aggregatessupporting
confidence: 70%
“…Optimized by Gaussian generalization theory, the length of the SDP molecule is 1.92 nm [ 46 ]. The small-angle X-ray scattering (SAXS) curves ( Figure 7 ) of both the vesicle solution and FeS 2 -vesicle solution samples show lamellar periodic diffraction peaks, indicating the presence of a vesicular bilayer structure.…”
Section: Resultsmentioning
confidence: 99%
“…The thickness of the vesicle bilayer is about 3.70 nm ( Figure S4 ), which is less than twice the length of the SDP molecule. This reveals that an interdigitated structure is adopted between the alkyl chains in the vesicular bilayers [ 46 , 47 , 48 ], with an interdigitated degree of 4.4% ( Figure S4 ). The thicknesses of the vesicle bilayers shift to 3.74 nm and 3.76 nm through the interaction with FeS 2 -1 ( Figure 7 a) and FeS 2 -60 ( Figure 7 b), with interdigitated degrees of 3.1% and 2.5%, respectively.…”
Section: Resultsmentioning
confidence: 99%